Altered AMPA receptor expression with treadmill exercise in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-lesioned mouse model of basal ganglia injury - VanLeeuwen, Jon-Eric; Petzinger, Giselle M.; Walsh, John P.; Akopian, Garnik K.; Vuckovic, Marta; Jakowec, Michael W. (Journal of neuroscience research, 2010)
Dopamine depletion leads to impaired motor performance and increased glutamatergic‐mediated hyperexcitability of medium spiny neurons in the basal ganglia. Intensive treadmill exercise improves motor performance in both saline treatment and the 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP) mouse model of Parkinson's disease. In the present study, we investigated the effect of high‐intensity treadmill exercise on changes in alpha‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptor (AMPAR) subunit expression, because these receptor channels confer the majority of fast excitatory neurotransmission in the brain, and their subunit composition provides a key mechanism for regulating synaptic strength and synaptic neuroplasticity and is important in modulating glutamatergic neurotransmission. Within the dorsolateral striatum of MPTP mice, treadmill exercise increased GluR2 subunit expression, with no significant effect on GluR1. Furthermore, neurophysiological studies demonstrated a reduction in the size of excitatory postsynaptic currents (EPSCs) in striatal medium spiny neurons (as determined by the input‐output relationship), reduced amplitude of spontaneous EPSCs, and a loss of polyamine‐sensitive inward rectification, all supportive of an increase in heteromeric AMPAR channels containing the GluR2 subunit. Phosphorylation of GluR2 at serine 880 in both saline‐treated and MPTP mice suggests that exercise may also influence AMPAR trafficking and thus synaptic strength within the striatum. Finally, treadmill exercise also altered flip isoforms of GluR2 and GluR1 mRNA transcripts. These findings suggest a role for AMPARs in mediating the beneficial effects of exercise and support the idea that adaptive changes in GluR2 subunit expression may be important in modulating experience‐dependent neuroplasticity of the injured basal ganglia. © 2009 Wiley‐Liss, Inc.